Disruption of the standard kinetochore in holocentric Cuscuta species - Neumann, Pavel; Oliveira, Ludmila; Jang, Tae-Soo; Novák, Petr; Koblížková, Andrea; Schubert, Veit; Houben, Andreas; Macas, Jiří (Proceedings of the National Academy of Sciences of the United States of America, 2023)
The segregation of chromosomes depends on the centromere. Most species are monocentric, with the centromere restricted to a single region per chromosome. In some organisms, the monocentric organization changed to holocentric, in which the centromere activity is distributed over the entire chromosome length. However, the causes and consequences of this transition are poorly understood. Here, we show that the transition in the genus Cuscuta was associated with dramatic changes in the kinetochore, a protein complex that mediates the attachment of chromosomes to microtubules. We found that in holocentric Cuscuta species, the KNL2 genes were lost; the CENP-C, KNL1, and ZWINT1 genes were truncated; the centromeric localization of CENH3, CENP-C, KNL1, MIS12, and NDC80 proteins was disrupted; and the spindle assembly checkpoint (SAC) degenerated. Our results demonstrate that holocentric Cuscuta species lost the ability to form a standard kinetochore and do not employ SAC to control the attachment of microtubules to chromosomes.
Keywords: Microtubules; monocentric; kinetochory; Chromosome Structures; Kinetochores; Chromosome Segregation; segregace chromozomů; centromere; holocentric; centromera; struktury chromozomu; kinetochore; Cuscuta; mikrotubuly; Centromere